Hypothetical Learning Trajectory for Prospective Elementary School Teachers in Learning Mathematics Assisted Artificial Intelligence Based on STEM - Efriani, Arvin; Arifin, Sujinal (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to analyze the process of designing Hypothetical Learning Trajectory of STEM Learning assisted by Artificial Intelligence (AI) for prospective teachers and its application in Madrasah Ibtidaiyah Mathematics courses. This research method used a design research (DR) with a qualitative approach. The subjects of this study were Prospective elementary school teachers Madrasah Ibtidaiyah students totaling 102 people from 25 groups. This study was divided into three stages, namely preparation of the experiment (design), implementation of the learning experiment, and retrospective analysis. The data collection techniques used in this study were observation, interviews, and questionnaires. Then the data was analyzed qualitatively with the stages of data reduction, data presentation, and drawing conclusions. The product of this study was an estimate of the STEM learning trajectory assisted by Artificial Intelligence (AI) which contained the following activities: exploring information, finding learning concepts, initiating ideas, and developing ideas. These four activities were carried out in a two-cycle experimental activity. After the activities were carried out, the prospective teacher students showed that they could design activities according to the stages given. There were 8 activity designs at the pilot experiment stage and 17 activity designs at the teaching experiment stage. The results of the activity design should be tested to suit the students' abilities.